Cognitive dysfunction among epilepsy patients and its associated factors - Naiem, Norazila (2017)
Background Epilepsy and cognition has an interchangeable relationship. The after-effect of seizure may cause disturbances or damages to one’s cognitive function. Multiple factors may adversely affect cognition in epilepsy, which can be grouped into sociodemographic, seizure-related, psychosocial and treatment factors. The objective of this study is to evaluate cognitive function (intelligence (IQ), memory and language) and factors associated with poor cognition among epilepsy patients in local setting. The knowledge of cognitive profile in epileptic patient will assist in improving quality of care and treatment of epilepsy patients. Methodology This was a cross-sectional study from November 2015 to November 2016 in Hospital USM. Epilepsy patients aged 16 to 65 years old who attended follow up at Neurology clinic, willing to participate with informed consent and fulfilled the inclusion criteria were selected. The largest sample size required for analysis was 111 subjects. Demographic data, seizure-related history and treatment were recorded. Patients underwent a set of neuropsychological assessment conducted by a trained personnel. The components tested were IQ, verbal memory and language. Wechsler Abbreviated Scale of Intelligence (WASI) was used to measure IQ level, while verbal memory was assessed using the Wechsler Memory Scale (WMS) and Verbal Fluency Test was used for language assessment. Variables obtained were analyzed using multiple logistic regression to determine the factors associated with cognitive dysfunction among epilepsy patients. Result 135 subjects were analyzed. The mean age of subject in this study was 30 ± 10.57 years old. The mean age of onset of epilepsy was 14 ± 4.82 years old. The mean duration of illness was 15 ± 7.51 years with mean attack of 3 ± 1.41 times per month and mean numbers of anti epileptic drug (AED) was 2 ± 0.85 drugs. Majority of subjects were Malay (71.9%). There were 70 female (51.9%) and 65 male (48.1%). 58.2% received higher education level and 60.7% were either not working or still studying. 72.6% had not experience status epilepticus (SE) of more than 30 minutes. No family history of epilepsy in 92.6% and absent of medical co morbidity in 85.9% of patients. The mean value of full scale of intelligence quotient (FSIQ) was 85.18 ± 14.27, total memory of 84.65 ± 12.91 and verbal fluency of 38.43 ± 8.57. Multivariate analysis revealed certain factors such as patient’s age, educational level, smoking status, duration of illness, number of AED and history of SE of more than 30 minutes were associated with impaired cognitive function among subjects studied. Conclusion There was significant association between cognitive dysfunction and sociodemographic factors such as current age, level of education and smoking status. There was also significant association with epilepsy characteristics such as age of onset, duration of illness, seizure frequency, history of SE of more than 30 minutes and number of AED used. We recommend an early recognition of patient’s cognitive profile via routine screening and neuropsychological assessment at the time of diagnosis. This would help to provide a baseline cognitive function. Any subsequent change in cognition among epilepsy patients either due to progression of the disease or the effect of treatmentshould also be measured. Early seizure control combined with cognitive rehabilitation may help to improve quality of life of the patients.